SANCTIONS ACCORDING TO INDONESIAN BUSINESS COMPETITION LAW POST JOB CREATION LAW: HAS IT REFLECTED THE LAW AS SOCIAL CONTROL? - Desi Apriani,; Zulherman Idris,; Nur Hidayat,; Ulfa Salsabila,; Bella Febria, (Proceeding International Conference on Social Sciences, 2026)
After the job creation law, the provisions for sanctions for violations of the law on the prohibition of monopolistic practices and unfair business competition have changed significantly. The provisions for administrative fine sanctions, for example, have undergone significant changes. This change has attracted the attention of researchers who study from various aspects, including from the accounting aspect. In law, there is one of the famous theories, that law is a tool of social control in order to better people's behavior. Based on that, the author sees that this study is important to be carried out so that the researcher will produce ideal conclusions and recommendations for future business competition law reform. This research is a normative legal research with a legislative, conceptual, and theoretical approach. The results of the study show that sanctions according to the business competition law after the job creation law do not support the functioning of the business competition law to achieve positive changes among business actors according to the purpose of the law to prevent the occurrence of monopoly practices and unfair business competition. The author suggests that the provisions of the fine sanction be reviewed and reviewed in the reform of the business competition law in the future so that the business competition law is able to form behavior and culture that prioritizes healthy business competition so that it has high competitiveness in the era of globalization.